Correlation of Core Muscle Strength and Lung Capacity among College-going Students: A Cross-sectional Observational Study - M Chinmayi; SN Tejaswini; Abeeshna Ashok (Journal of Clinical and Diagnostic Research)
Introduction: The abdominal muscles play a crucial role in posture, trunk stability, and respiration. They regulate Intra-abdominal Pressure (IAP), support spinal stability, and function as accessory respiratory muscles during increased respiratory demand. Pulmonary Function Tests (PFTs), particularly spirometry, assess lung function by measuring airflow and lung capacity. Given the involvement of abdominal muscles in respiration, their strength may influence pulmonary function. Aim: To explore the correlation between abdominal muscle strength and respiratory function, focussing on the Forced Expiratory Volume in one second (FEV1)/Forced Vital Capacity (FVC), ratio and Maximum Voluntary Ventilation (MVV) in healthy adults. Materials and Methods: A cross-sectional observational study was conducted at JSS College of Physiotherapy, Mysore, Karnataka, India. The study was carried out over a six-month period, from July 2021 to December 2021.Participants were recruited through convenience sampling from the college population. A total of 22 healthy college-going students, aged 18-25 years, were included.Participants were informed about the nature and purpose of the study and provided written informed consent. The procedure included, assessment of abdominal muscle strength using a hand-held dynamometer. The test was performed in a standardised supine position on a treatment table inclined at 30°, with lower limbs strapped for stability. Three trials were conducted with 5 second rest intervals, and the average was recorded. PFT was done using a computerised spirometer (EasyOne PC). Parameters recorded included FEV1/FVC ratio, MVV and Tidal Volume (TV). The Pearson correlation coefficient (“r”) was utilised to determine the relationship between abdominal strength, FEV1/FVC, MVV, TV, age, height, weight, and Body Mass Index (BMI). A p-value of less than 0.05 was deemed significant. Results: A significant positive correlation was found between abdominal strength and MVV in the 6th second (r=0.420, p=0.049) and TV (r=0.506, p=0.016), indicating that individuals with greater abdominal strength exhibited better ventilatory capacity. However, FEV1/FVC (r=0.196, p=0.381) and overall MVV (r=0.354, p=0.106) did not show statistically significant correlations. Conclusion: This study explored the correlation between core muscle strength and lung capacity among college-going students. The findings indicate a significant correlation between core strength and pulmonary function, suggesting that stronger core muscles may contribute to better lung capacity.